Gain-of-function mutation of tristetraprolin impairs negative feedback control of macrophages in vitro yet has overwhelmingly anti-inflammatory consequences in vivo - O'Neil, JD; Ross, EA; Ridley, ML; Ding, Q; Tang, T; Rosner, DR; Crowley, T; Malhi, D; Dean, JL; Smallie, T; Buckley, CD; Clark, AR (American Society for Microbiology, 2017)
The mRNA-destabilizing factor tristetraprolin (TTP) binds in a sequence-specific manner to the 3' untranslated regions of many proinflammatory mRNAs and recruits complexes of nucleases to promote rapid mRNA turnover. Mice lacking TTP develop a severe, spontaneous inflammatory syndrome characterized by the overexpression of tumor necrosis factor and other inflammatory mediators. However, TTP also employs the same mechanism to inhibit the expression of the potent anti-inflammatory cytokine interleukin 10 (IL-10). Perturbation of TTP function may therefore have mixed effects on inflammatory responses, either increasing or decreasing the expression of proinflammatory factors via direct or indirect mechanisms. We recently described a knock-in mouse strain in which the substitution of 2 amino acids of the endogenous TTP protein renders it constitutively active as an mRNA-destabilizing factor. Here we investigate the impact on the IL-10-mediated anti-inflammatory response. It is shown that the gain-of-function mutation of TTP impairs IL-10-mediated negative feedback control of macrophage function in vitro However, the in vivo effects of TTP mutation are uniformly anti-inflammatory despite the decreased expression of IL-10.